Exploring the Integration of AI and Cloud Computing: Navigating Opportunities and Overcoming Challenges - Musawer Hakimi; Ghulam Ali Amiri; Safiullah Jalalzai; Farid Ahmad Darmel; Zakirullah Ezam (Universitas Pendidikan Nasional, 2024)
This research seeks to establish how the integration of cloud computing and artificial intelligence identifies opportunities across operational efficiency, cost reduction, and innovation acceleration. This study seeks to establish how this integration is revolutionizing traditional business models and dealing with emerging security, privacy, and regulatory challenges. The applied method in this research was a systematic review strategy whose sources of data will be chosen from IEEE Xplore, Wiley Online Library, Springer, and ScienceDirect. The literature review focused on publications from 2019 to 2024 to deduce current findings that remain relevant. Results have shown that artificial intelligence, when integrated with cloud computing, would significantly enhance operational efficiency through process optimization and reduced cost using scalable cloud solutions. This also provides a greater pace of innovation by allowing real-time data processing and advanced analytics. However, such integration has a specific set of security and privacy concerns related to breaches and compliance with regulations in continuous evolution. It concludes that, though large, the benefits of AI and cloud computing integration must be reined in by strong security measures, updating regulatory frameworks, and continued research into ethical implications.